Do transformational leadership and work engagement matter for job performance in luxury hotels? Exploring the role of leaders’ managerial skills - Aftab, Junaid; Sarwar, Huma; Kiran, Alina; Abid, Nabila; Ahmad, Suraya (Emerald Publishing Limited, 2022)
Purpose - The paper aimed to explore the underlying work engagement role in transformational leadership and employees' job performance relationships. Moreover, this study also looked at the moderation of leaders' managerial skills in the transformational leadership and work engagement nexus.